A Connecticut Yankee in King Arthur's court - Twain, Mark, 1835-1910.; Inge, M. Thomas (New York : Oxford University Press, 1998)
An annotated edition of American author Mark Twain's 1889 social and technological satire in which Hank Morgan, a nineteenth-century American, is transported to sixth-century England. Also includes several of Dan Beard's original illustrations for the novel, as well as a scholarly introduction, a Twain chronology, and a selected bibliography.
Includes bibliographical references (p. [xxii]-xxiii).
Young Adult
Keywords: Americans -- Travel -- Great Britain -- Fiction; Arthurian romances -- Adaptations; Knights and knighthood -- Great Britain -- Fiction; Time travel -- Fiction; Americans -- Great Britain -- Fiction; Arthurian romances -- Adaptations; Historical fiction; Knights and knighthood -- Fiction; Time travel -- Fiction; Fantastic fiction